2020
DOI: 10.3390/ijerph17249201
|View full text |Cite
|
Sign up to set email alerts
|

Insights Gained in the Aftermath of the COVID-19 Pandemic: A Follow-Up Survey of a Recreational Training Program, Focusing on Sense of Coherence and Sleep Quality

Abstract: The original aim of this study was a follow-up assessment of a recreational program running for six months (September 2019–February 2020) within controlled conditions. Following the arrival of the COVID-19 pandemic, the survey acquired a new goal: how do the subjects of the follow-up sampling experience this severe stress situation, and in this experience, what role does physical activity and a salutogenetic sense of coherence play. Austrian women (N = 53) took part in the training program, whose physical cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
2
10
0
1
Order By: Relevance
“…In line with existing literature ( Szovák et al, 2020 ; Schäfer et al, 2019 ), having a stronger SoC was associated with lesser stress symptoms in nursing students. Most of the faculty members' SoC levels were also associated with lower SASRQ scores, except for Laotian and Vietnamese faculty members who showed statistically insignificant positive correlations between the two variables.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with existing literature ( Szovák et al, 2020 ; Schäfer et al, 2019 ), having a stronger SoC was associated with lesser stress symptoms in nursing students. Most of the faculty members' SoC levels were also associated with lower SASRQ scores, except for Laotian and Vietnamese faculty members who showed statistically insignificant positive correlations between the two variables.…”
Section: Discussionsupporting
confidence: 90%
“…The SoC helps an individual to mobilize resources that aid them in managing stressors ( Mittelmark and Bauer, 2017 ). A strong SoC is associated with pro-health behaviors, reduced negative impact from stressors and lower post-traumatic stress disorder (PTSD) symptom severity ( Szovák et al, 2020 ; Schäfer et al, 2019 ). Individuals with strong SoC can understand and manage their internal and external environments better, helping them cope with stress efficiently ( Szovák et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of the latter paper explicitly recommended interventions aimed at enhancing SOC in vulnerable individuals. The validity of this approach was tested in a study of a recreational intervention in a small sample of women (n = 53), which found that over a period of 6 months, physical activity was associated with an increase in SOC; however, initial SOC was itself associated with a greater likelihood of adhering to the exercise regimen, suggesting a bi-directional relationship (Szovak et al, 2020).…”
Section: Evidence For the Relevance Of Salutogenic Factors During The Covid-19 Pandemicmentioning
confidence: 99%
“…A study of 53 Austrian women shows that physical exercise prescribed by personal training has been shown to be successful in reducing the deterioration of sleep quality due to the stress caused by the pandemic situation [52]. One study investigated changes in physical activity, sleep time and body weight before and during COVID-19 in South Korea and found that participants who slept less than 7 h decreased by 3.6%, while those who slept more than 9 h increased this value.…”
Section: Previous Studiesmentioning
confidence: 99%